Combinations of Hd2 and Hd4 genes determine rice adaptability to Heilongjiang Province, northern limit of China. Issue 8 (18th March 2015) - Li, Xiufeng; Liu, Huazhao; Wang, Maoqing; Liu, Hualong; Tian, Xiaojie; Zhou, Wenjia; Lü, Tianxiao; Wang, Zhenyu; Chu, Chengcai; Fang, Jun; Bu, Qingyun
Abstract: Heading date is a key trait in rice domestication and adaption, and a number of quantitative trait loci (QTLs) have been identified. The rice ( Oryza sativa L.) cultivars in the Heilongjiang Province, the northernmost region of China, have to flower extremely early to fulfill their life cycle. However, the critical genes or different gene combinations controlling early flowering in this region have not been determined. QTL and candidate gene analysis revealed that Hd2/Ghd7.1 / OsPRR37 plays a major role in controlling rice distribution in Heilongjiang. Further association analysis with a collection of rice cultivars demonstrated that another three major QTL genes ( Hd4/Ghd7, Hd5/DTH8/Ghd8, and Hd1 ) also participate in regulating heading date under natural long day (LD) conditions. Hd2/Ghd7.1 / OsPRR37 and Hd4/Ghd7 are two major QTLs and function additively. With the northward rice cultivation, the Hd2/Ghd7.1 / OsPRR37 and Hd4/Ghd7 haplotypes became non‐functional alleles. Hd1 might be non‐functional in most Heilongjiang rice varieties, implying that recessive hd1 were selected during local rice breeding. Non‐functional Hd5/DTH8/Ghd8 is very rare, but constitutes a potential target for breeding extremely early flowering cultivars. Our results indicated that diverse genetic combinations of Hd1, Hd2, Hd4, and Hd5 determined the different distribution of rice varieties in this northernmost province of China.